Determination of the class of dynamic models of target operations - Lutsenko, Igor; Fomovskaya, Elena; Serdiuk, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
Existing classes of models of operations are limited to the class of accounting models. As a basis for the research, a simple model of the target operation was used. Expert estimates of input products of the operation are reduced in this model to the start time, and expert estimates of output products of the operation - to the time of its completion. The well-known class of operations provides the possibility of compact storage of information in a database and identification of these operations. However, as the experience of the studies showed, these models could not be used to develop the efficiency indicator. To overcome this restriction, the class of dynamic models of target operations was identified. The class of models of system operations, in which the input and output of the operation products are reduced to comparable measures, and the dynamics of the bound state of product operations is determined on the whole range of research, is defined in the paper as the class of dynamic models of target operations. The results of research of test operations using the comprehensive profitability indicator, which was obtained using the features of the dynamic model have shown that such indicator can solve the problems of identification in the area, formerly the part of the area of restrictions for conventional economic indicators.